Updating Student Profiles in Adaptive Mobile Learning using ASP.net MVC, dotNetRDF, Turtle, and the Semantic Web - Hamada, Samir E; Alkore Alshalabi, Ibrahim; Elleithy, Khaled; Badara, Ioana; Moslehpour, Saeid (International Journal of Interactive Mobile Technologies (iJIM), 2017)
In this paper, we present a conceptual framework for using the Semantic Web to get student data from other educational institutions, enabling the educational institutions to communicate and exchange student data and then use this information to adjust the students’ profiles and modify their learning paths. Semantic Web will create a more personalized dynamic course for each student, according to his/her ability, educational level, and experience.